2002
DOI: 10.1128/jb.184.18.5104-5112.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of Cyanobacterium Insertion Element ISY100inEscherichia coli

Abstract: The genome of the cyanobacterium Synechocystis sp. strain PCC6803 has nine kinds of insertion sequence (IS) elements, of which ISY100 in 22 copies is the most abundant. A typical ISY100 member is 947 bp long and has imperfect terminal inverted repeat sequences. It has an open reading frame encoding a 282-amino-acid protein that appears to have partial homology with the transposase encoded by a bacterial IS, IS630, indicating that ISY100 belongs to the IS630 family. To determine whether ISY100 has transposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…However, based on previous reports that many IS110/IS492 family elements do not generate duplication of the target site sequence upon insertion (14,23,30), we cannot exclude the possibility that 1,279-bp-long IS621 is inserted into the target site without duplication. We have been trying to develop a system for transposing IS621 into the target plasmid with or without a REP sequence by using methods that have been used previously to transpose IS elements, such as IS1, IS3, and ISY100 (41,42,48), but we have failed to do so. IS492, an IS110/IS492 family element, is known to generate circular IS492 molecules with an extra 5-bp sequence immediately adjacent to the element (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on previous reports that many IS110/IS492 family elements do not generate duplication of the target site sequence upon insertion (14,23,30), we cannot exclude the possibility that 1,279-bp-long IS621 is inserted into the target site without duplication. We have been trying to develop a system for transposing IS621 into the target plasmid with or without a REP sequence by using methods that have been used previously to transpose IS elements, such as IS1, IS3, and ISY100 (41,42,48), but we have failed to do so. IS492, an IS110/IS492 family element, is known to generate circular IS492 molecules with an extra 5-bp sequence immediately adjacent to the element (35).…”
Section: Discussionmentioning
confidence: 99%
“…Southern hybridization was carried out against PCR products on 0.8% agarose gels according to Urasaki et al (2002), using a p-SINE1 probe that had been labeled with digoxigenin using a DIG-oligonucleotide 3' end labeling kit (Roche).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…IS14999 is thought not to need any host factors in its transposition because it has been reported that IS630/Tc1 superfamily elements do not require any host factors (Craig, 1997;Urasaki et al, 2002). This would be an advantage for using IS14999 as a tool for genetic manipulation in various bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Tc1/mariner family elements, like IS630 family elements, also have conserved DDE or DDD triad amino acids as an essential part of their catalytic site, and mutations in the triad abolished transposase activity (Lohe et al, 1997). Consequently, these two families form a mega-family, the IS630/Tc1 superfamily, whose elements share a similar signature sequence or motif in the catalytic domain of their respective transposases (Shao & Tu, 2001;Urasaki et al, 2002). The only difference is that Tc1/mariner family elements appear to be excised from their donor molecules, leaving an empty site with an extra sequence, called a footprint (Plasterk, 1996), like those of other element families.…”
Section: Discussionmentioning
confidence: 99%